Пошаговое объяснение:
1) а - 2; а - 1 <--- а ---> а + 1; а + 2
2) у + 1; у + 2 <--- у + 3 ---> у + 4; у + 5
два попередніх для "а"
а-2 ; a-1
два наступних для "а"
а+1 ; a+2
два попередніх для "y+3" -
y+3-2=y+1 ; y+3-1=y+2
y+3+1 =y+4; y+3+2=y+5
Пошаговое объяснение:
1) а - 2; а - 1 <--- а ---> а + 1; а + 2
2) у + 1; у + 2 <--- у + 3 ---> у + 4; у + 5
Пошаговое объяснение:
два попередніх для "а"
а-2 ; a-1
два наступних для "а"
а+1 ; a+2
два попередніх для "y+3" -
y+3-2=y+1 ; y+3-1=y+2
два наступних для "а"
y+3+1 =y+4; y+3+2=y+5